Grain boundaries in periodic vs. in aperiodic crystals composed of colloids with preferred binding angles - Weigel, Robert; Schmiedeberg, Michael (Molecular Systems Design & Engineering, 2025)
Using a modified phase field crystal model that we have recently introduced [Weigel et al., Modelling and Simulation in Materials Science and Engineering, 2022, 30, 074003], we study grain boundaries that occur in two-dimensional structures composed of particles with preferred binding angles like patchy colloids. In the case of structures with a triangular order, we show how particles with a 5-fold rotational symmetry that differs from the usual 6-fold coordination of a particle in bulk affect the energy of the dislocations in the grain boundaries. Furthermore, for quasicrystals we find that the dislocation pairs recombine easily and the grain boundaries disappear. However, the resulting structure usually possesses a lot of phasonic strain. Our results demonstrate that the preferred symmetry of a particle is important for grain boundaries, and that periodic and aperiodic structures may differ in how stable their domain boundaries ar